A discussion on the influence that Lean Inventory Management has on Supply Chain - Ayush Garg (Innovative Research Thoughts, 2023)
On the other hand, the purpose of this article is to offer an overview of lean inventory management and its influence on the performance of supply chain operations. A discussion of the notion of lean inventory management and its principles is presented in this article. These concepts include the reduction of waste, the elimination of unneeded inventory, and the improvement of flow. Additionally, the paper illustrates the advantages of applying lean inventory management in a supply chain, including enhanced customer service, shorter lead times, and higher profitability. These benefits are highlighted in the study. Lower costs associated with keeping inventory, fewer stockouts, and increased production efficiency are all potential outcomes that may be achieved via the application of lean inventory management principles. The study also examines the difficulties that are involved with adopting lean inventory management in a supply chain. These difficulties include resistance to change, a lack of staff buy-in, and the need for a culture shift toward continuous improvement. Based on the results of this study, it seems that the use of lean inventory management strategies may result in enhanced supply chain performance, which in turn can lead to greater levels of customer satisfaction and profitability. Therefore, in order to maximise the efficiency of their supply chain operations, businesses have to give serious consideration to adopting lean inventory management strategies.